2019
DOI: 10.3390/en12204015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Preliminary Performance Analysis of a New Solar Thermal Reverse Osmosis Desalination Process

Abstract: Reverse osmosis (RO) is a desalination technique that is commonly preferred because of its low energy consumption. In this paper, an innovative, thermally powered RO desalination process is presented. This new thermo-hydraulic process uses solar thermal energy in order to realize the pressurization of the saltwater beyond its osmotic pressure to allow its desalination. This pressurization is enabled thanks to a piston or a membrane set in motion in a reservoir by a working fluid that follows a thermodynamic cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The author used a genetic-simulated annealing algorithm to numerically solve the model and found that a robust scheduling scheme can optimize the reverse osmosis system better than a static scheduling scheme. In 2019, Lacroix [12] introduced a new type of thermal power reverse osmosis desalination process. This new thermal hydraulic process used solar energy to pressurize sea water and made it exceed osmotic pressure, to desalinate it.…”
Section: Introductionmentioning
confidence: 99%
“…The author used a genetic-simulated annealing algorithm to numerically solve the model and found that a robust scheduling scheme can optimize the reverse osmosis system better than a static scheduling scheme. In 2019, Lacroix [12] introduced a new type of thermal power reverse osmosis desalination process. This new thermal hydraulic process used solar energy to pressurize sea water and made it exceed osmotic pressure, to desalinate it.…”
Section: Introductionmentioning
confidence: 99%
“…Solar water distilling devices are classified into several models-e.g., prism models, pyramid models, and centralized collector models [8]. Nevertheless, these devices cannot produce large amounts of distilled water, as reported by Badran [2], Heck et al [6], Cappelletti [9], and Aburideh et al [10]. Cappelletti [9] performed an experimental study on a plastic solar still and obtained 1.7-1.8 L/d of distilled water.…”
Section: Introductionmentioning
confidence: 95%
“…Energies 2021, 14, 4844 2 of 15 Meanwhile, a powerful device to turn seawater into freshwater is RO. This kind of device has been also investigated by previous researchers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Sun et al [26] performed a two-phase flow test on a circulating solar collector tube at the Zijingang Campus of Zhejiang University, and assembled the collector tube by means of horizontal series connections to simulate the heat-collecting efficiency of the collector tube at different flow velocities. Lacroix et al [27] introduced a new type of thermal power reverse osmosis desalination process. This new thermal hydraulic process used solar energy to pressurize sea water and made it exceed osmotic pressure, to desalinate it.…”
Section: Introductionmentioning
confidence: 99%